Pre-Examination Study Preparation and Its Effect on the Summative Test Score in General Mathematics of Grade 11 Senior High School Students of Dr. Carlos S. Lanting College: Pre-Examination Study Preparation and Its Effect on the Summative Test Score in General Mathematics of Grade 11 Senior High School Students - Malangen, Ardian D. (Future Science / FSH-PH Publications, 2021)
Examination weeks are the peaks of an academic year. The paper-and-pen test determines whether the learners are able to attain the specific educational standards set by the pedagogical curriculum they follow. The study wants to determine the pre-examination study preparation and its effect on the summative test score in general mathematics of grade 11 senior high school students of Dr. Carlos S. Lanting College. This study centers on two factors, the frequency and strategy of the student used on their pre-examination preparation. The descriptive and quantitative method of research is used in this study. As a results and conclusions in terms of pre- examination frequency, majority of the grade 11 senior high school students allotted one day (69.30%) before the examination 30 minutes to one hour (52.60%) as review time. The most preferred pre-examination study strategy of the respondents is rereading their textbooks and/or lecture notes (3.37 frequently). There is no significant positive correlation between the pre-examination study frequency and the summative test results, there is a significant positive correlation between Tracks and the summative test results and between the study strategy (rereading textbooks/lecture notes, and seeking assistance to parents) and the summative test results of the Grade 11 senior high school students of Dr. Carlos S. Lanting College. Lastly, avoid cramming, students spend at least three days of review before the examination for a better learning in a well managed time and engage their selves to the most significant favored review strategies that will give an impressive test results.